2000
DOI: 10.2754/avb200069010051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Characteristics of Cats Affected by Feline Infectious Peritonitis

Abstract: A set of 180 hospitalized or outdoor feline patients was examined for the presence of antibodies to feline coronavirus (FeCoV) and clinical signs of feline infectious peritonitis (FIP). The numbers of serologically and clinically positive cats were 55 (30.6%) and 35, respectively. The effusive and noneffusive forms of FIP were diagnosed in 24 and 11 animals, respectively. The most apparent signs, irrespective of the form of infection, included anorexia, lethargy, ischemic mucosae, and undernutrition. Hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
(18 reference statements)
2
10
1
2
Order By: Relevance
“…In contrast, the low T cell counts detected in catteries with high prevalence of FIP suggests that the decreased number of these cells might be involved in differences in disease susceptibility among cats. This hypothesis is supported by the results recorded in cats with FIP, which had extensive lymphopenia with decreased numbers within all the lymphocyte subsets, in agreement with previous reports on blood (Knotek et al, 2000) and on tissues, where advanced FIP lesions were found to have less CD4 þ lymphocytes than recent ones (Paltrinieri et al, 1998). Compared to controls, the percentage of CD5 þ þ CD21 þ cells was significantly lower in cats with FIP, while the percentage of CD4 þ þ CD8 þ cells was close to the percentage of CD5 þ cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, the low T cell counts detected in catteries with high prevalence of FIP suggests that the decreased number of these cells might be involved in differences in disease susceptibility among cats. This hypothesis is supported by the results recorded in cats with FIP, which had extensive lymphopenia with decreased numbers within all the lymphocyte subsets, in agreement with previous reports on blood (Knotek et al, 2000) and on tissues, where advanced FIP lesions were found to have less CD4 þ lymphocytes than recent ones (Paltrinieri et al, 1998). Compared to controls, the percentage of CD5 þ þ CD21 þ cells was significantly lower in cats with FIP, while the percentage of CD4 þ þ CD8 þ cells was close to the percentage of CD5 þ cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, the possibility that in FIP-affected cats the percentage of non-T-non-B lymphocytes increases cannot be excluded. These findings, together with previously reported defects of T cell function (Gunn-Moore et al, 1998;Knotek et al, 2000) might play an important role in the development of FIP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hyposialylation has been found to be specific in FIP, but not in clinically healthy, FCoV infected cats (Ceciliani et al, 2004;Paltrinieri et al, 2008). Although previous report, performed with methods different from those reported in this study, suggested that phagocytosis is not suppressed in cats wit FIP (Knotek et al, 2000), the hyposialylation of fAGP, which we found to down-regulate phagocytosis, may influence the clinical outcome of FCoV infection by inducing a failure of cellular responses to the virus. Macrophages and neutrophils are involved in FIP immunopathology, being the most abundant, while hardly effective, populations in pyogranulomatous lesions (Kipar et al, 1998;Paltrinieri et al, 1998).…”
Section: Discussioncontrasting
confidence: 68%
“…The presence of FeLV p27 antigen was detected by microtiter plate ELISA (IDEXX PetChek Ò , IDEXX, Portland, ME, USA) and results classified as positive (including equivocal) or negative (Lutz et al, 1983). Although foxes were not tested for FIV, FeLV and FCoV/FIPV, as these disease agents are feline-specific, these pathogens may compromise immunity in infected cats (Hoover and Mullins, 1991;Knotek et al, 2000;Pedersen and Barlough, 1991), making cats more susceptible to opportunistic infections with other disease agents (such as CDV, FPLV, FCV or T. gondii) that could be transmitted to island foxes.…”
Section: Serologic Testingmentioning
confidence: 99%